Acute safety, efficacy, and advantages of a novel cryoballoon ablation system for pulmonary vein isolation in patients with paroxysmal atrial fibrillation: initial clinical experience. Issue 8 (17th March 2021) - Anic, Ante; Lever, Nigel; Martin, Andrew; Breskovic, Toni; Sulkin, Matthew S; Duffy, Elizabeth; Saliba, Walid I; Niebauer, Mark J; Wazni, Oussama M; Varma, Niraj
Abstract: Aims: Cryoballoon pulmonary vein isolation (PVI) is a safe and effective treatment for atrial fibrillation (AF). Current limitations include incomplete vein occlusion due to balloon rigidity and inconsistent electrogram recording, which impairs identification of isolation. We aimed to evaluate the acute safety and performance of a novel cryoballoon system. Methods and results: The system includes a steerable sheath, mapping catheter, and a balloon that maintains uniform inflation pressure and size following initiation of ablation. Protocol-directed cryoablation was delivered for 180 s for isolation documented in ≤60 s, otherwise freeze duration was 240 s. Primary endpoints were acute safety and vein isolation. Pulmonary vein isolation was confirmed at ≥30 min post-isolation. Data were compared across vein locations. Thirty patients with paroxysmal AF were enrolled at two centres and underwent PVI. Pulmonary vein isolation was achieved with cryoablation only in 100% of veins (120/120). Nadir temperature was −53.1 ± 5.3°C. The number of applications to achieve PVI was 1.4 ± 0.4 per vein. Of the 120 veins, 89 were isolated with a single cryothermal application (10/30 patients required only 4 total cryoablations). There were no procedural- or device-related serious adverse events at 30 days post-procedure. A subset (24/30) of patients was followed for 1-year and 71% (17/24) remained free of atrial arrhythmias. Six patients with arrhythmia recurrence were remapped and three had durable PVI for all four veins. Conclusion: In this first human experience, the novel cryoballoon platform was safe, efficacious, and demonstrated a high proportion of successful single ablation isolation.